MENGEMBANGKAN KECERDASAN SOSIAL ANAK USIA DINI MELALUI PERMAINAN TRADISIONAL - MEHA, NEHRU (JURNAL PENDIDIKAN ANAK USIA DINI, 2011)
Age 0-6 years old is crucial age in the formation of character and intelligence of a child. Efforts to develop the full potential of early childhood should begin for the growth and development of children achieved optimally. Childhood is a very beautiful time to be remembered. The play is a dye of childhood a topic that is often told. Unfortunately, the plays unique traditional start children rarely played in this era and replaced with modern play equipment such as play station. Whereas traditional play is a means to develop childrens ability. Ancient traditional play is saying it should be celebrated and examined matters relating to education. Many of the play the people of Indonesia that the terms with the meaning of education of children toward logical thinking. Traditional play also can develop childrens intelligence and inculcate positive values. Organization of early childhood education requires the right approach to optimize the full potential of intelligence of children. There are many approaches in early childhood education, including through local cultural approach that is peoples play or traditional play, in addition, also as an effort to preserve it for not going extinct.Keywords: social intelligence, social development, traditional play